Fairy friends - Pitts, Sorrel (London : Ladybird Books ., 2017)
GENERAL FICTION (CHILDREN'S / TEENAGE). Lily and Rose are fairies. They like helping their friends. Patch is a bad elf. Will he be friends with Lily and Rose? Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language
Keywords: English - Book; Ladybird English books